Research on the Relationship between the Development of Artificial Intelligence Technology and the Change of Education Goals - Ishak, Nor Asniza; Jiang, Chuan Xing (International Journal of Intelligent Systems and Applications in Engineering, 2022)
The future of education is inextricably linked to advances in new technologies and the computing capabilities of new intelligent machines. In this study, we are going to research on the relationship between the development of artificial intelligence technology and the change of education Goals. This paper investigates the phenomenon of the emergence of AI in teaching and learning in changes of education goals. It looks into facilitate a better understanding of emerging technologies on how students learn as well as how institutions teach and evolve. Recent technological breakthroughs and the increasing speed with which new technologies are being adopted in education are investigated in order to forecast the future purpose of teaching in a world where AI is incorporated in the universities. The study identify some challenges for educational institutions and student learning in the implementation of technology for teaching, learning, and administration. The study proposed remote supervision algorithm for analyzing the relationship between the enhancement of artificial intelligence and change of education goals. The results proved that the suggested algorithm outperforms better than the existing algorithms.